Competency-Based Recruitment and Selection for Enhancing Human Resource Performance in Indonesian Higher Education Institutions - Joko Nugroho (AL-ISHLAH: Jurnal Pendidikan, 2026)
Human resource performance plays a critical role in supporting academic quality, administrative effectiveness, and competitive advantage of higher education institutions in Indonesia. Traditional recruitment practices often emphasize academic qualifications and seniority rather than demonstrated job competencies. This has led to mismatches between employee capabilities and institutional needs. Competency-based recruitment and selection offers a structured approach to identifying candidates with relevant behavioral, technical, and managerial competencies. This study employs a Systematic Literature Review (SLR) approach following PRISMA guidelines. Academic sources published between 2013–2025 were retrieved from Scopus, Google Scholar, and institutional repositories using keyword combinations such as “competency-based recruitment,” “competency model,” “human resources,” “higher education,” and “Indonesia.” A total of 87 studies were initially identified; after screening for relevance, methodology suitability, and duplication, 26 studies were selected for full analysis. Data were synthesized through thematic coding focusing on competency frameworks, recruitment schemes, and HR performance indicators. The review indicates that competency-based recruitment and selection practices yield measurable improvements in employee productivity, role clarity, and organizational fit within Indonesian higher education institutions. Thematic patterns reveal that institutions implementing structured competency frameworks—such as behavioral event interviews, psychometric talent assessments, and competency matrices—achieved up to 25–40% performance improvement in selected units. Moreover, alignment between institutional strategic goals and competency requirements resulted in lower turnover rates and stronger employee engagement. Challenges identified include limited HR capability in competency mapping, inconsistent implementation standards, and cultural resistance toward merit-based selection. Findings demonstrate that competency-based recruitment is not only theoretically beneficial but practically impactful when supported by institutional readiness and HR strategic alignment. The success of implementation depends on top-level commitment, HR professional development, and institutional transformation toward performance-based culture. While competency-based models reduce subjectivity and favoritism, they require sustainable investment in assessment tools, competency modeling, and applicant evaluation standardization. Future research should incorporate empirical case studies across larger samples of universities and integrate digital HR analytics for competency tracking. Competency-based recruitment and selection significantly contributes to improving human resource performance in Indonesian higher education institutions. Adoption of this approach enables better alignment between employee competencies and organizational goals, ultimately enhancing institutional effectiveness. To maximize impact, universities must institutionalize competency frameworks, strengthen HR capacity, and foster merit-based hiring culture.